2010
DOI: 10.5012/bkcs.2010.31.8.2207
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stimulated Conductivity in Cellulose Triacetate-Multiwalled Carbon Nanotube Polymer Films

Abstract: This paper describes the preparation and study of thermally stimulated discharge conductivity (TSDC) study of cellulose triacetate (CTA) -multiwalled carbon nanotubes (MWNTs) film thermoelectrets. TSDC has been carried out in the temperature range 308 -503 K and at four different polarizing fields. The conductivity of the polymer blends increased with increase in temperature showing a semi-conducting behavior. The apparent activation energy also showed a pronounced effect with the increase in the content of MW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In a similar fashion the use biopolymers as in our earlier research, [28][29][30]34,35 it is expected that the conductivity values should increase. Despite increasing the concentration of the biopolymer (PCL), the conductivity increases for a particular concentration (10-40 wt %) and further increase in the same causes the decrease in the conductivity.…”
Section: -51mentioning
confidence: 99%
See 3 more Smart Citations
“…In a similar fashion the use biopolymers as in our earlier research, [28][29][30]34,35 it is expected that the conductivity values should increase. Despite increasing the concentration of the biopolymer (PCL), the conductivity increases for a particular concentration (10-40 wt %) and further increase in the same causes the decrease in the conductivity.…”
Section: -51mentioning
confidence: 99%
“…The characterization of the composites was described in earlier studies. [28][29][30][31][32][33][34][35][36][37] The FT-IR spectra of the samples were measured by a Perkin Elmer (model 783) IR spectrometer in KBr medium at room temperature. The UV-vis spectra were recorded by a Shimadzu UV-vis-NIR spectrophotometer (UV-3101PC) in chloroform.…”
Section: -34mentioning
confidence: 99%
See 2 more Smart Citations
“…However, these methods cause a significant decrease in the optical transparency of the polymer films and increase the birefringence. Although some studies of CTA/filler composites have been reported, the birefringence of such reinforced CTA composites has not been revealed. Reinforcement that can preserve both the transparency and birefringence of CTA is required.…”
Section: Introductionmentioning
confidence: 99%